ILRI, livestock research, and the global development agenda - Smith, Jimmy W. (International Livestock Research Institute, 2014)
In this film, Jimmy Smith, the director general of the International Livestock Research Institute (ILRI), talks about the global development agenda and the roles of livestock, and ILRI within it.